Splenic Rupture After Colonoscopy - Lalor, Peter F. (Society of Laparoendoscopic Surgeons, 2007)
Colonoscopy is a familiar and well-tolerated procedure and is widely used as a diagnostic and therapeutic modality by both gastroenterologists and surgeons. Although perforation and hemorrhage are the most common complications, splenic injury or rupture is a rare but potentially lethal complication. We report a case of splenic rupture diagnosed 18 hours after colonoscopy, which required emergent splenectomy. We also reviewed over 39 other cases of splenic rupture or injury after colonoscopy reported in the English literature. Despite being an infrequent complication, splenic rupture warrants a high degree of clinical suspicion critical to prompt diagnosis. Most patients present with symptoms within 24 hours after colonoscopy, although delayed presentation days later has been described. CT scan of the abdomen is the radiological study of choice to evaluate colonoscopic complications. Splenic injury can be managed conservatively or with arterial embolization depending on the extent of trauma, but splenectomy remains definitive management. Clinical criteria are the primary determinants in choosing operative therapy over observation. Herein, possible risk factors for splenic trauma during colonoscopy are identified, and clinical outcomes are evaluated.